Cycling Exercise Affects the Expression of Apoptosis-Associated microRNAs after Spinal Cord Injury in Rats - Liu, Gang (2010)
There are two major aspects to a spinal cord injury (SCI): an acute, primary mechanical trauma and a progressive phase of secondary tissue damage provoked by inflammation, excitotoxicity, apoptosis and demyelination. MicroRNAs (miRs) are small, ~22 nucleotide, non-protein-coding RNAs that function at the post-transcriptional level to regulate gene expression. They have important roles in homeostatic processes such as cell proliferation and programmed cell death. In the injured rat spinal cord we performed an expression analysis of miRs and their downstream targets involved in apoptotic pathways and used post-injury cycling exercise to test for activity dependent plasticity of miR expression. We show that SCI results in increased expression of miR Let-7a and miR16 while exercise leads to elevated levels of miR21 and decreased levels of miR15b. These changes in miR expression are correlated with changes in expression of their target genes: pro-apoptotic (decreased PTEN, PDCD4 and RAS mRNA) and anti-apoptotic (increased Bcl-2 mRNA) target genes. This is accompanied by a down regulation of mRNA for caspase-7 and caspase-9 and reduced levels of caspase-7 protein. These results indicates possible beneficial effects of exercise through action on multiple miRs and their targets that contribute to the functional regulation of apoptosis after SCI.